Dinaphtho boron oxide structure derivative and preparation method and application thereof
By designing TADF materials with dinaphthalene-boro oxygen structure, the problems of harsh synthesis conditions of existing multi-resonance TADF materials and difficulty in taking into account luminous efficiency and luminous intensity are solved, and efficient, stable luminous performance and long-life electroluminescent devices are achieved.
Patent Information
- Application Number
- CN202510172576.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-17
AI Technical Summary
The synthesis conditions of existing multi-resonance TADF materials are harsh and it is difficult to take into account both luminous efficiency and luminous intensity, resulting in a short roll-off of efficiency and device life, which limits its commercial development.
A dinaphthalene-boro oxygen structure derivative was designed. By introducing O atoms and B atoms into the main structure and phenyl substitution, a conjugated system with a three-dimensional configuration is formed. The separation of HOMO and LUMO is achieved by using the valence electron difference effect between B atoms and O atoms, reducing the relaxation degree of excited state structures and improving the crossover efficiency between reverse systems.
A narrow half-maximum width of the emission spectrum is achieved, which improves luminous efficiency and luminous brightness, reduces the roll-off efficiency of electroluminescent devices, extends the service life of the device, simplifies the synthesis process, and reduces production costs.
Smart Images

Figure CN119613438A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic luminescent materials and semiconductors, and in particular relates to dinaphthoboryloxy structure derivatives and preparation methods and applications thereof. Background Art
[0002] In recent years, organic light-emitting diodes (OLEDs) have become a hot research direction in the field of lighting and display due to their excellent characteristics such as self-luminescence, high brightness, high contrast, see-through, wearable, foldable, low energy consumption, wide viewing angle and low temperature resistance. With the development of science and technology, researchers have developed the third generation of OLED luminescent materials - thermally activated delayed fluorescence (TADF) materials. TADF materials can achieve a theoretical internal quantum efficiency of 100% by utilizing the upconversion process from triplet to singlet, thereby achieving efficient luminescence. Classical TADF materials are usually composed of donor-acceptor structures, and there is a large degree of distortion between the donor and the acceptor. This structure can reduce the single-triplet energy level difference of the material and realize the effective antisystem crossing process of triplet excitons, so that the exciton utilization rate can reach up to 100%. However, due to the large relaxation energy of the structure during the excitation and emission process of this type of molecule, the emission spectrum of the material has a half-peak width of 70~100nm, which affects the luminescence purity of the material. Therefore, in addition to constructing a highly rigid molecular structure type, how to make the molecules have a higher luminous efficiency while obtaining a narrower spectrum band is of great significance in the development of OLED materials.
[0003] At present, the problem of spectral bandwidth is solved by designing a basic unit of a structural compound with a BRB configuration to stack multiple times to form a multi-resonance unit mode. However, multi-resonance TADF materials often have a large single-triplet energy level difference, resulting in a small anti-system crossing rate of the material. Finally, when applied to OLED devices, they show a serious efficiency roll-off (specifically the problem of reduced luminous efficiency of electroluminescent devices due to exciton quenching at high current density) and a short device life, which is not conducive to its commercial development. Therefore, this technology still needs to be improved and developed.
[0004] China's public patent CN113402537 A realizes the multiple resonance effect by constructing multiple B-containing small vibration units in the molecule, thereby realizing the maximum improvement of the luminous efficiency of the material without increasing the luminous wavelength of the material. From the practical results, this method has indeed achieved the expectations at the beginning of material design in terms of regulating the wavelength and improving the luminous efficiency of the material; but its shortcomings are also obvious. First of all, the introduction of boron elements into the molecule itself is relatively demanding, and there are fewer means of synthesis; if multiple B-containing luminescent units are to be constructed in a single molecule, it is even more difficult from a synthetic perspective. Secondly, based on the coordination characteristics of boron, the construction of molecules in each subunit in the molecular design of the multiple resonance structure type is often similar, which leads to such materials with good plane symmetry, strong rigidity, and easy to form crystals. This type of material shows a higher boiling point and easier crystallization in use, which hinders its practical application. In addition, although the multiple BRB configuration has a high luminous efficiency, the luminous brightness of a single subunit is low, and the luminous intensity of the overall device is significantly low, which is still a large gap from the market-oriented practical promotion and application. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a dinaphthoboryloxy structure derivative and a preparation method and application thereof, so as to solve the technical problems that the synthesis conditions of the existing multi-resonance TADF materials are harsh and it is difficult to balance the luminous efficiency and luminous intensity.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: In the first aspect of the present invention, a dinaphthoboryloxy structure derivative is disclosed, the structure of which is shown in general formula 1:
[0007] Where: As the main structure; R1 and R2 are independently selected from C2-C8 alkenyl, C2-C8 Si-containing alkenyl, C2-C8 alkynyl, C2-C8 Si-containing alkynyl, C8-C 30 Aromatic secondary amines, substituted or unsubstituted C6~C 40 aryl or substituted or unsubstituted C4~C 40 The substituted or unsubstituted C4~C 40 The heteroatom in the heteroaryl is one or more of O, S, N, Si and Ge, and the substituent is selected from C1~C 10 an alkyl group, a cyano group, an acetonitrile group, a F atom, a D atom, a deuterated methyl group, a deuterated tert-butyl group, a dimethylamino group, a vinyl group, an allyl group, a propenyl group, a styryl group, a phenylallyl group, a phenyl group or a benzyl group; The bonding mode of R1, R2 to the main structure is single bond bonding.
[0008] The second aspect of the present invention discloses a method for preparing the above-mentioned dinaphthoboryloxy structure derivative, comprising the following steps: Step 1: Using 6-bromo-2-naphthol and p-chlorobenzenesulfonic acid as raw materials, an etherification reaction is carried out through intermolecular dehydration to obtain an intermediate Mn-1; Step 2: The intermediate Mn-1 reacts with the active form of iodine to obtain the intermediate Mn-2 through electrophilic substitution reaction; Step 3, the intermediate Mn-2 undergoes intramolecular ring closure under the action of n-butyl lithium to obtain the intermediate Mn; Step 4: The intermediate Mn is subjected to an affinity substitution reaction or a Suzuki reaction to obtain a dinaphthoboryl derivative.
[0009] The third aspect of the present invention discloses the use of the above-mentioned dinaphthoboroxy structure derivatives in the preparation of electroluminescent devices.
[0010] The fourth aspect of the present invention discloses an electroluminescent device, comprising an anode layer, a cathode layer and a light-emitting layer located between the anode layer and the cathode layer, wherein the light-emitting layer is made of a host light-emitting material and a guest light-emitting material, and the guest light-emitting material is selected from the above-mentioned dinaphthoboryl oxide structure derivatives.
[0011] Preferably, the mass percentage of the guest luminescent material in the entire luminescent layer material is 0.1% to 3%.
[0012] Preferably, a hole injection layer, a hole transport layer and an electron blocking layer are provided between the anode layer and the light-emitting layer, and a hole blocking layer, an electron transport layer and an electron injection layer are provided between the light-emitting layer and the cathode layer.
[0013] A fifth aspect of the present invention discloses a display panel, which includes the above-mentioned electroluminescent device.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The dinaphthoboryloxy structure derivative provided by the present invention has a parent core structure such as the general formula 1, wherein the 7-position of the six-membered ring of the main structure is designed as an O atom, the 14-position is designed as a B atom, and a phenyl group is substituted at the 14-position, so that the large π bond system of the original planar structure is transformed into a conjugated system with a stereo configuration (such as Figure 1As shown). On the one hand, the valence electron difference effect between the B atom and the O atom can be used to achieve the separation of HOMO and LUMO. At the same time, the hybrid fused ring unit of the B atom and the O atom has a rigid skeleton structure, which can reduce the degree of structural relaxation of the excited state, thereby achieving a narrow half-peak width. On the other hand, the boron-containing heterocyclic system has a strong electron-withdrawing effect, which makes the frontier orbital overlap between the electron donor connected to it smaller, and achieves a small energy level difference between the S1 state and the T1 state, thereby achieving reverse intersystem crossing under thermal stimulation conditions. In addition, the compound has a significant asymmetric stereo conformation characteristic in space, which reduces the intermolecular stacking during film formation, improves the film-forming performance during molecular evaporation, and significantly improves the luminescence consistency, thereby effectively improving the device stability and device yield. Performance tests have proved that the application of this type of compound as a guest luminescent material in the luminescent layer of an OLED device can effectively reduce the roll-off efficiency of the electroluminescent device, improve the luminescent brightness, and extend the service life of the electroluminescent device.
[0015] The preparation method of the dinaphthoboryloxy structure derivative provided by the present invention has the advantages that the reaction raw materials are easily available and inexpensive, the reaction process is conventional, the single-step reaction yield is high, the cost can be effectively controlled, and large-scale and sustainable production is expected to be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The main structure design diagram of the dinaphthoboryloxy structure derivative of the present invention; wherein arrow 7 indicates the 7th position of the six-membered ring of the main structure, and arrow 14 indicates the 14th position of the six-membered ring of the main structure; Figure 2 is a cross-sectional view of the organic electroluminescent device of the present invention; Figure 3 is the nuclear magnetic spectrum of compound 1 of the present invention; Figure 4 is the NMR spectrum of compound 137 of the present invention; Figure 5 is the NMR spectrum of compound 278 of the present invention; Figure 6 It is the NMR spectrum of compound 386 of the present invention.
[0017] Description of reference numerals: 1-substrate layer, 2-anode layer, 3-hole injection layer, 4-hole transport layer, 5-electron blocking layer, 6-light-emitting layer, 7-hole blocking layer, 8-electron transport layer, 9-electron injection layer, 10-cathode layer, 11-covering layer. DETAILED DESCRIPTION
[0018] The following describes the embodiments of the present invention through specific examples. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments. The details in this specification can also be based on different viewpoints and applications. Various modifications or changes without departing from the spirit of the present invention are within the scope of the present invention.
[0019] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0020] In this article, unless otherwise specified, "D" in the structural formula stands for "deuterium".
[0021] The present invention provides a dinaphthoboryloxy structure derivative, the structure of which is shown in general formula 1:
[0022] Where: As the main structure; R1 and R2 are independently selected from C2-C8 alkenyl, C2-C8 Si-containing alkenyl, C2-C8 alkynyl, C2-C8 Si-containing alkynyl, C8-C 30 Aromatic secondary amines, substituted or unsubstituted C6~C 40 aryl or substituted or unsubstituted C4~C 40 The substituted or unsubstituted C4~C 40 The heteroatom in the heteroaryl is one or more of O, S, N, Si and Ge, and the substituent is selected from C1~C 10 an alkyl group, a cyano group, an acetonitrile group, a F atom, a D atom, a deuterated methyl group, a deuterated tert-butyl group, a dimethylamino group, a vinyl group, an allyl group, a propenyl group, a styryl group, a phenylallyl group, a phenyl group or a benzyl group; The bonding mode between R1 and R2 and the main structure is single bond; In the group To replace the position.
[0023] Preferably, R1 and R2 are independently selected from any one of the following groups and their derivatives:
[0024]
[0025]
[0026]
[0027] .
[0029] The present invention provides a method for preparing the above-mentioned dinaphthoboryloxy structure derivative, and the reaction formula is as follows:
[0030] Step 1: Using 6-bromo-2-naphthol and p-chlorobenzenesulfonic acid as raw materials, an etherification reaction is carried out through intermolecular dehydration to obtain an intermediate Mn-1; Step 2: iodine element can generate active forms of iodine under the action of hydrogen peroxide, and these active forms can react with intermediate Mn-1 through electrophilic substitution to obtain intermediate Mn-2; Step 3, the iodine of the intermediate Mn-2 is lithiolated under the action of n-butyl lithium, and then the borate is attacked to achieve intramolecular ring closure to obtain the intermediate Mn; Step 4: Using the intermediate Mn as a raw material, an affinity substitution reaction or a Suzuki reaction is performed to obtain a derivative as shown in the general formula 1.
[0031] The present invention provides an organic electroluminescent device, such as Figure 2 As shown, from the anode to the cathode direction, it includes a substrate layer 1, an anode layer 2, a hole injection layer 3, a hole transport layer 4, an electron blocking layer 5, a light-emitting layer 6, a hole blocking layer 7, an electron transport layer 8, an electron injection layer 9, a cathode layer 10 and a covering layer 11.
[0032] The substrate layer 1 needs to have the characteristics of high mechanical strength, excellent thermal stability, excellent water resistance and excellent transparency; preferably, it is made of polyethylene terephthalate (PET) plastic.
[0033] As the anode layer 2, in order to enable holes to be smoothly injected into the organic layer, the anode material is preferably a material with a large work function. Specific examples of the anode material that can be used in the present invention include metals such as vanadium, chromium, copper, zinc, and gold, or their alloys; oxides such as zinc oxide, aluminum oxide, or tin dioxide; conductive polymers such as polypyrrole and polyaniline; As the functional organic layer, including hole injection layer 3, hole transport layer 4, electron blocking layer 5, light emitting layer 6, hole blocking layer 7, electron transport layer 8 and electron injection layer 9, the functional organic layer can be formed on the electrode by vacuum thermal evaporation, spin coating, printing and other means or methods, and the compounds used for each organic layer except the light emitting layer 6 can be organic small molecules, organic macromolecules and polymers, and their combinations. The materials used for the hole injection layer 3, hole transport layer 4, electron blocking layer 5, hole blocking layer 7, electron transport layer 8 and electron injection layer 9 are selected from the corresponding functional layer materials with excellent cost performance in the industry, and the compatibility between the functional layers needs to be determined through a series of tests and screening processes; As the material of the hole injection layer 3, MoO3 is preferred; The material of the hole transport layer 4 may be selected from one of the following materials: ; The material of the electron blocking layer 5 may be selected from one of the following materials: ; The luminescent layer 6 is formed by composite co-evaporation of a main luminescent material and a guest luminescent material; wherein the main luminescent material is selected from , , , or The guest luminescent material is selected from any one of the compounds having a higher triplet energy as shown in the general formula 1. The mass fraction of the guest luminescent material in the entire luminescent layer 6 is 0.1% to 3.0%.
[0034] The material of the hole blocking layer 7 can be selected from One of; As the material of the electron transport layer 8, one of the following materials may be selected: ; As the material of the electron injection layer 9 , LiF is preferable.
[0035] As the cathode layer 10, in order to facilitate the injection of electrons into the functional organic layer, the cathode material is preferably a material with a small work function. Specific examples of the cathode material that can be used in the present invention include metals such as magnesium, calcium, sodium, potassium, titanium, indium, yttrium, lithium, gadolinium, aluminum, silver, tin and lead, or alloys thereof: multilayer structure materials such as LiF-A1 or LiO2-A1, Mg-Al, Mg-Ag, etc.; As the cover layer 11, the refractive index of the surface of the cathode layer 10 can be improved, thereby increasing the light extraction rate; preferably preparation.
[0036] The present invention also provides a method for preparing the above-mentioned organic electroluminescent device, comprising adhering an anode layer 2 on a substrate layer 1 after pretreatment and cleaning, and then sequentially vapor-depositing a hole injection layer 3, a hole transport layer 4, an electron blocking layer 5, a light-emitting layer 6, a hole blocking layer 7, an electron transport layer 8 and an electron injection layer 9 with set thicknesses under low temperature conditions, and then continuously sputtering a cathode layer 10 and a covering layer 11 under low temperature conditions, and finally packaging the test device using conventional device testing and packaging means to obtain an organic electroluminescent device.
[0037] The present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the contents described in the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application. In addition, those skilled in the art can refer to the preparation method of the compound of the above-mentioned general formula 1 and the following specific examples, in combination with intermediates M1 to M4, to prepare compounds 1 to 401.
[0038] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The process equipment or devices not specifically specified in the following examples are all conventional equipment or devices in the art. The various raw materials used in the following examples, unless otherwise specified, are conventional commercial products, and their specifications are conventional specifications in the art.
[0039] The structural formula of the representative compound of the dinaphthoboryloxy structure derivative provided by the present invention is as follows:
[0040]
[0041]
[0042]
[0043]
[0044]
[0045]
[0046]
[0047]
[0048]
[0049]
[0050]
[0051]
[0052]
[0053]
[0054]
[0055]
[0056]
[0057]
[0058]
[0059]
[0060]
[0061]
[0062]
[0063]
[0064]
[0065]
[0066]
[0067]
[0068]
[0069]
[0070]
[0071]
[0072]
[0073]
[0074]
[0075]
[0076]
[0077]
[0078] .
[0079] Example 1 (Synthesis of Compound 1)
[0080] Step 1: Operation process: Under argon protection, add 6-bromo-2-naphthol (223 g, 1.0 mol), 2.0 L o-dichlorobenzene and p-chlorobenzenesulfonic acid (19.3 g, 0.1 mol) to a 5 L three-necked flask, heat the reaction solution to 180°C, and continue the reaction for 10 h until the reaction is complete. After the reaction is completed, cool the reaction solution to room temperature, concentrate the reaction solvent under reduced pressure, add 3 L dichloromethane to dilute, wash with 3 L saturated sodium bicarbonate, dry and concentrate the organic phase, and purify the residue by silica gel column chromatography (dichloromethane / petroleum ether) to obtain intermediate M1-1, weighing 156 g, with a yield of 73%, HPLC purity of 98%, and LC-MS showing a molecular weight of 429.0.
[0081] Step 2: Operation process: Add M1-1 (128 g, 0.3 mol) and 1.5 L of 2-methyltetrahydrofuran solution to a 5 L three-necked flask, stir, add iodine (152 g, 0.6 mol), continue stirring, and slowly add 30% hydrogen peroxide (H2O2; 170 g, 1.5 mol). Stir the reaction mixture at room temperature for 24 h. After the reaction is completed, wash the reaction mixture with 3 L of NaHSO3 and extract with dichloromethane (3×2 L). The organic phase is washed with water (1×3 L), dried over anhydrous sodium sulfate, and concentrated. The residue is purified by silica gel column chromatography (acetonitrile / n-heptane) to obtain intermediate M1-2, weighing 186 g, with a yield of 91%, HPLC purity of 98%, and LC-MS showing a molecular weight of 680.7.
[0082] Step 3: Operation process: Under argon protection, add M1-2 (170 g, 0.25 mol) and 1.5 L THF to a 5 L three-necked flask, cool the reaction solution to below -78 °C, add 2.5 mol / L n-butyl lithium (200 mL, 0.5 mol), continue to stir the reaction solution for 1 h after the addition is complete, slowly add 200 mL of dimethyl phenylboronate (37 g, 0.25 mol) in THF, stir the reaction for 1 h after the addition is complete, transfer to room temperature, and continue to react for 20 h until the reaction is complete. After the reaction is completed, the reaction system is concentrated at low temperature to remove most of the THF, 3 L of dichloromethane is added to dilute, washed with 3 L of water, the organic phase is dried and concentrated, and the residue is purified by silica gel column chromatography (dichloromethane / petroleum ether) to obtain the intermediate M1, weighing 51 g, with a yield of 40%, HPLC purity of 98%, and LC-MS showing a molecular weight of 515.0.
[0083] Step 4: Operation process: Under argon protection, add M1 (5.1 g, 0.01 mol), phenylboronic acid (2.6 g, 0.021 mol), 40 mL THF, 10 mL H2O and K2CO3 (5.5 g, 0.04 mol) into a 100 mL three-necked flask, stir and heat to 40°C, add Pd(PPh3)4 (0.2 g, 0.2 mmol) after the solution is clarified, and then heat the reaction solution to 70°C and continue the reaction for 12 h until the reaction is completed. The reaction solution was cooled to room temperature, extracted with ethyl acetate (EA) for multiple times, the organic phases were combined, dried over anhydrous magnesium sulfate, filtered and concentrated, and passed through a silica gel column (dichloromethane / petroleum ether) to obtain compound 1, weighing 4.1 g, with a yield of 80%, HPLC content of 99%, LC-MS showing a molecular weight of 509.2, and the nuclear magnetic spectrum as shown below Figure 3 shown.
[0084] Example 2 (Synthesis of Compound 137)
[0085] Step 1: Operation process: The synthesis process of M2-1 refers to the synthesis process of M1-1, replacing 6-bromo-2-naphthol (223 g, 1.0 mol) with 7-bromo-2-naphthol (223 g, 1.0 mol) to obtain intermediate M2-1, weighing 154 g, with a yield of 72%, HPLC purity of 98%, and LC-MS showing a molecular weight of 429.0.
[0086] Step 2: Operation process: The synthesis process of M2-2 refers to the synthesis process of M1-1 to M1-2, replacing M1-1 (128 g, 0.3 mol) with M2-1 (128 g, 0.3 mol) to obtain the intermediate M2-2, weighing 184 g, with a yield of 90%, HPLC purity of 98%, and LC-MS showing a molecular weight of 680.7.
[0087] Step 3: Operation process: The synthesis process of M2 refers to the synthesis process from M1-2 to M1, replacing M1-2 (170 g, 0.25 mol) with M2-2 (170 g, 0.25 mol) to obtain intermediate M2, weighing 50 g, with a yield of 39%, HPLC purity of 98%, and LC-MS showing a molecular weight of 515.0.
[0088] Step 4: Operation process: Under inert atmosphere, M2 (5.1 g, 0.01 mol), deuterated carbazole (3.7 g, 0.021 mol) and 50 mL toluene were added to a 100 mL three-necked flask, stirred until the solution was clear, Pd2(dba)3 (0.18 g, 0.2 mmol), Am-phos (0.13 g, 0.5 mmol), sodium tert-butoxide (3.8 g, 0.04 mmol) were added, the reaction solution was heated to 120°C, and the reaction was continued for 10 h. After the reaction was completed, diatomaceous earth was used for hot filtration, the filtrate was cooled to room temperature, purified water was added for washing, the organic phase was retained after separation, the aqueous phase was extracted with ethyl acetate, the organic phases were combined, the organic phases were dried over anhydrous magnesium sulfate, concentrated, and passed through a column (dichloromethane / petroleum ether) to obtain compound 137, weighing 5.3 g, with a yield of 76%, HPLC content of 99%, LC-MS showing a molecular weight of 703.4, and the nuclear magnetic spectrum as shown below Figure 4 shown.
[0089] Example 3 (Synthesis of Compound 278)
[0090] Step 1: Operation process: The synthesis process of M3-1 refers to the synthesis process of M1-1, replacing 6-bromo-2-naphthol (223 g, 1.0 mol) with 3-bromo-2-naphthol (223 g, 1.0 mol) to obtain intermediate M3-1, weighing 150 g, with a yield of 70%, HPLC purity of 98%, and LC-MS showing a molecular weight of 429.0.
[0091] Step 2: Operation process: The synthesis process of M3-2 refers to the synthesis process of M1-1 to M1-2, replacing M1-1 (128 g, 0.3 mol) with M3-1 (128 g, 0.3 mol) to obtain the intermediate M3-2, weighing 186 g, with a yield of 91%, HPLC purity of 98%, and LC-MS showing a molecular weight of 680.7.
[0092] Step 3: Operation process: The synthesis process of M3 refers to the synthesis process from M1-2 to M1, replacing M1-2 (170 g, 0.25 mol) with M3-2 (170 g, 0.25 mol) to obtain intermediate M3, weighing 50 g, with a yield of 39%, HPLC purity of 98%, and LC-MS showing a molecular weight of 515.0.
[0093] Step 4: Operation process: Under inert atmosphere, M3 (5.1 g, 0.01 mol), 3-trimethylsilylallylboronic acid (3.3 g, 0.021 mol), 50 mL 1,4-dioxane, K2CO3 (4.1 g, 0.03 mol) and CsF (3.04 g, 0.02 mol) were added to a 100 mL three-necked flask and stirred until the solution was clear. Pd2(dppf)Cl2 (0.37 g, 0.5 mmol) was added, the reaction solution was heated to 80°C, and the reaction was continued for 16 h. After the reaction was completed, diatomaceous earth was used for hot filtration, the filter cake was washed with ethyl acetate, the filtrate was cooled to room temperature, purified water was added for washing, the organic phase was retained after separation, and the aqueous phase was extracted with ethyl acetate. The organic phase was dried over anhydrous magnesium sulfate, concentrated, and passed through a column (dichloromethane / petroleum ether) to obtain compound 278 with a weight of 4.4 g, yield 75%, HPLC content 99%, LC-MS showed molecular weight 581.3, NMR spectrum as shown Figure 5 shown.
[0094] Example 4 (Synthesis of Compound 386)
[0095] Step 1: Operation process: The synthesis process of M4-1 refers to the synthesis process of M1-1, replacing 6-bromo-2-naphthol (223 g, 1.0 mol) with 4-bromo-2-naphthol (223 g, 1.0 mol) to obtain intermediate M4-1, weighing 152 g, with a yield of 71%, HPLC purity of 98%, and LC-MS showing a molecular weight of 429.0.
[0096] Step 2: Operation process: The synthesis process of M4-2 refers to the synthesis process of M1-1 to M1-2, replacing M1-1 (128 g, 0.3 mol) with M4-1 (128 g, 0.3 mol) to obtain the intermediate M4-2, weighing 182 g, with a yield of 89%, HPLC purity of 98%, and LC-MS showing a molecular weight of 680.7.
[0097] Step 3: Operation process: The synthesis process of M4 refers to the synthesis process from M1-2 to M1, replacing M1-2 (170 g, 0.25 mol) with M4-2 (170 g, 0.25 mol) to obtain intermediate M4, weighing 49 g, with a yield of 38%, HPLC purity of 98%, and LC-MS showing a molecular weight of 515.0.
[0098] Step 4: Operation process: The synthesis process of compound 386 refers to step 4 of the synthesis process of compound 137, replacing M2 (5.1 g, 0.01 mol) with M4 (5.1 g, 0.01 mol), and replacing deuterated carbazole (3.7 g, 0.021 mol) with N-methyl-1-(perfluorophenyl)methanamine (4.4 g, 0.021 mol) to obtain compound 386, weighing 5.7 g, with a yield of 74%, a purity of 99% by HPLC, a molecular weight of 775.2 by LC-MS, and a nuclear magnetic resonance spectrum as shown below: Figure 6 shown.
[0099] According to the structural information of the light-emitting layer 6 of the electroluminescent device given in Table 1, the electroluminescent devices of Examples 5 to 15 and Comparative Examples 1 to 3 were prepared.
[0100] Table 1 Structure of the light-emitting layer and hole blocking layer of electroluminescent devices
[0101] Example 5 (Electroluminescent device containing compound 1) An electroluminescent device containing compound 1, which comprises polyethylene terephthalate (PET) plastic, indium tin oxide (ITO) conductive glass, MoO3, HT-2, EB-2, light-emitting layer 6, HB-2, ET-2, LiF, Al-Mg (Al:Mg=9:1) and CPL in order from anode to cathode; In the light-emitting layer 6, PH-3 is used as the main light-emitting material, and compound 1 is used as the guest light-emitting material. The mass ratio of PH-3 to compound 1 is 98:2.
[0102] The method for preparing the electroluminescent device containing compound 1 comprises the following steps: 1. Use 1.5 mm PET plastic as substrate layer 1 and 0.15 mm ITO conductive glass as anode layer 2. Use alkali washing, pure water washing, drying, and then ultraviolet-ozone washing to remove organic residues on the surface of PET plastic and ITO conductive glass.
[0103] 2. A layer of ITO conductive glass is adhered to PET plastic, and a vacuum evaporation device is used to evaporate MoO3 with a thickness of 20 nm as a hole injection layer 3, and then HT-2 with a thickness of 45 nm is evaporated as a hole transport layer 4, followed by EB-2 with a thickness of 30 nm as an electron blocking layer 5, and a luminescent layer 6 formed by PH-3 and compound 1 with a mass ratio of 98:2 is continuously evaporated on EB-2, and then HB-2 with a thickness of 10 nm is continuously evaporated on the luminescent layer 6 as a hole blocking layer 7, and then ET-2 with a thickness of 30 nm is continuously evaporated as an electron transport layer 8, and then LiF with a thickness of 16 nm is continuously evaporated on the electron transport layer 8 as an electron injection layer 9. After the electron injection layer 9 is evaporated, a 10 nm thick Al-Mg (Al:Mg=9:1) alloy is sputtered as a cathode layer 10 by low-temperature sputtering, and finally a 40 nm thick CPL is continuously evaporated on the cathode layer 10 as a covering layer 11.
[0104] 3. MoO3, HT-2, EB-2, light-emitting layer 6, HB-2, ET-2 and LiF layer are vacuum packaged to obtain an organic electroluminescent device.
[0105] Example 6 The difference from Example 5 is that in the light-emitting layer 6, the mass ratio of PH-3 to compound 1 is 99.9:0.1.
[0106] Example 7 The difference from Example 5 is that in the light-emitting layer 6, the mass ratio of PH-3 to compound 1 is 97:3.
[0107] Embodiment 8 to Embodiment 17 The difference from Example 5 is that in the light-emitting layer 6 , compounds 101, 201, 14, 114, 214, 336, 37, 137, 237 and 347 are selected as guest light-emitting materials of the light-emitting layer 6 , respectively.
[0108] Comparative Example 1 The difference from Example 5 is that in the light-emitting layer 6, conventional materials are used. As a guest luminescent material.
[0109] The structure of the electroluminescent device is: PET substrate / ITO / MoO3(20 nm) / HT-2(45 nm) / EB-2(30 nm) / PH-3: C1=98:2(60 nm) / HB-2(10 nm) / ET-2(30 nm) / LiF(16 nm) / Al: Mg=9:1(10 nm) / CPL(40 nm).
[0110] Comparative Example 2 The difference from Example 5 is that in the light-emitting layer 6, conventional materials are used. As a guest luminescent material.
[0111] The structure of the electroluminescent device is: PET substrate / ITO / MoO3(20 nm) / HT-2(45 nm) / EB-2(30nm) / PH-3: C1-16=98:2 (60 nm) / HB-2(10 nm) / ET-2 (30 nm) / LiF(16 nm) / Al:Mg=9:1(10 nm) / CPL(40 nm).
[0112] Comparative Example 3 The difference from Example 5 is that in the light-emitting layer 6, conventional materials are used. As the guest luminescent material, the mass ratio of the host luminescent material to the guest luminescent material is 98:2.
[0113] The structure of the electroluminescent device is: PET substrate / ITO / MoO3(20 nm) / HT-2(45 nm) / EB-2(30nm) / PH-3: C1-117=98:2 (60 nm) / HB-2(10 nm) / ET-2 (30 nm) / LiF(16 nm) / Al: Mg=9:1 (10 nm) / CPL(40 nm).
[0114] The electroluminescent devices in the above embodiments and comparative examples were prepared into samples of 30 mm×30 mm, and then the anode and cathode were connected using a driving circuit known in the industry under the same device manufacturing process conditions, and the OLED was characterized, and the life was calculated from the current / voltage / luminous density characteristic line showing Lambertian emission characteristics. The test results are shown in Table 2.
[0115] Table 2 Electroluminescent device performance test results
[0116] (Note: The current density during the test is 10 mA / cm, and LT95 refers to the time it takes for the device brightness to decay to 95% of the initial brightness) It can be seen from the test data in Table 2 that 1) compared with the test devices prepared from the guest luminescent materials C1, C1-16 and C1-117 in the control group (Comparative Examples 1 to 3), the test devices prepared from the dinaphthoboroxy structure derivative prepared by the present method have obvious advantages in comprehensive luminous efficiency, with a roll-off efficiency reduced by about 40% and a service life extended by about 2 times. 2) Comparison of Examples 5 to 7 with Comparative Examples 1 to 3 shows that when the mass ratio of the guest material in the luminescent layer 6 is in the range of 0.1% to 3%, the comprehensive luminescent performance is improved, and the device prepared with a mass ratio of 2% of the guest material in the luminescent layer 6 has the best luminescent performance. 3) When R1 and R2 in the structure shown in the general formula 1 are fully fluorinated substituents, the device prepared with the corresponding compound as the guest luminescent material (Example 10 to Example 13) is much better than the electroluminescent device prepared with R1 and R2 as phenyl substituents (Example 5 to Example 9) in terms of comprehensive luminescence performance, which may be due to the fact that the fluorine atom has a lone pair of electrons and can form p-π conjugation, thereby increasing the range of electron activity and enhancing the luminescence brightness. 4) When R1 and R2 in the structure shown in the general formula 1 are fully deuterated substituents, the device prepared with R1 and R2 as phenyl substituents (Example 14 to Example 17) is significantly improved in terms of comprehensive luminescence performance compared to the electroluminescent device prepared with R1 and R2 as phenyl substituents (Example 5 to Example 9), which may be due to the fact that after the "D" atom is introduced into the compound molecule, the spin-orbit coupling of the compound molecule will be enhanced, which will increase the intersystem crossing (ISC) ability of the electrons in the molecule, increase the radiative transition rate of the molecule, and reduce the non-radiative transition rate, thereby facilitating the improvement of the quantum efficiency of the guest luminescent material.
[0117] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A dinaphthoboryloxy structure derivative, characterized in that: The structure is shown in general formula 1: Where: As the main structure; R1 and R2 are independently selected from C2-C8 alkenyl, C2-C8 Si-containing alkenyl, C2-C8 alkynyl, C2-C8 Si-containing alkynyl, C8-C 30 Aromatic secondary amines, substituted or unsubstituted C6~C 40 aryl or substituted or unsubstituted C4~C 40 The substituted or unsubstituted C4~C 40 The heteroatom in the heteroaryl is one or more of O, S, N, Si and Ge, and the substituent is selected from C1~C 10 an alkyl group, a cyano group, an acetonitrile group, a F atom, a D atom, a deuterated methyl group, a deuterated tert-butyl group, a dimethylamino group, a vinyl group, an allyl group, a propenyl group, a styryl group, a phenylallyl group, a phenyl group or a benzyl group; The bonding mode of R1, R2 to the main structure is single bond bonding.
2. The dinaphthoboryloxy structure derivative according to claim 1, characterized in that: R1 and R2 are independently selected from the following groups and their derivatives: ; Among them, the To replace the position.
3. The dinaphthoboryloxy structure derivative according to claim 1 or 2, characterized in that: The dinaphthoboryl oxide structure derivative is selected from the following compounds: 。 4. The method for preparing a dinaphthoboryloxy structure derivative according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: Using 6-bromo-2-naphthol and p-chlorobenzenesulfonic acid as raw materials, an etherification reaction is carried out through intermolecular dehydration to obtain an intermediate Mn-1; Step 2: The intermediate Mn-1 reacts with the active form of iodine to obtain the intermediate Mn-2 through electrophilic substitution reaction; Step 3, the intermediate Mn-2 undergoes intramolecular ring closure under the action of n-butyl lithium to obtain the intermediate Mn; Step 4: The intermediate Mn is subjected to an affinity substitution reaction or a Suzuki reaction to obtain a dinaphthoboryl derivative.
5. Use of the dinaphthoboryloxy structure derivative according to any one of claims 1 to 3 in the preparation of an electroluminescent device.
6. An electroluminescent device, characterized in that: The invention comprises an anode layer (2), a cathode layer (10) and a light-emitting layer (6) located between the anode layer (2) and the cathode layer (10), wherein the light-emitting layer (6) is made of a host light-emitting material and a guest light-emitting material, and the guest light-emitting material is selected from the dinaphthoboryl oxide structure derivative according to any one of claims 1 to 3.
7. An electroluminescent device according to claim 6, characterized in that: The mass percentage of the guest luminescent material in the entire luminescent layer (6) is 0.1% to 3%.
8. An electroluminescent device according to claim 6, characterized in that: The main luminescent material is selected from , , , or .
9. An electroluminescent device according to any one of claims 6 to 8, characterized in that: A hole injection layer (3), a hole transport layer (4) and an electron blocking layer (5) are provided between the anode layer (2) and the light-emitting layer (6); and a hole blocking layer (7), an electron transport layer (8) and an electron injection layer (9) are provided between the light-emitting layer (6) and the cathode layer (10).
10. A display panel, characterized in that: The display panel comprises the electroluminescent device according to any one of claims 6 to 9.
Citation Information
Patent Citations
Organic compound and application thereof
CN113402537A
Polycyclic aromatic compound
CN110719914A
Organic electroluminescent materials and devices
CN115197249A
Carbazole derivative containing boron atoms and application thereof
CN116120353A
Naphthalene ketone derivative and electroluminescent device based on same
CN119241418A
Cited By
Seven-membered ring boron oxide compound, preparation method thereof and electroluminescent device
CN120554403A
A seven-membered ring boron oxide compound, preparation method thereof, and electroluminescent device
CN120554403B